Khai thác tiềm năng kinh tế du lịch ở các tỉnh Duyên hải miền Trung - Đỗ, Thanh Phương (2011)
Tác giả: Đỗ Thanh Phương; Phạm Hảo, PGS,TS; Phạm Tiến Lực, ThS; Phạm Thanh Khiết, PGS,TS -- Từ khóa: Du lịch; Kinh tế du lịch